An energy storage planning method for improving the security of receiving-end system considering the selection of power conversion systems - Haibo Zhang; Kai Wei; Yukang Hu; Quan Hu (International Journal of Electrical Power & Energy Systems)
China's power demand in high load density areas is satisfied by a centralized feed of several large-capacity HVDC links, forming a typical receiving-end system, which is facing problems such as shortage of dynamic reactive power and increased risk of commutation failure. Electrochemical energy storage (ES) has characteristics such as strong dynamic active and reactive power regulation ability, rapid response and flexible control mode, making it a high-quality resource in improving the security of the receiving-end system. Therefore, it is necessary to carry out research on the methods of planning of ES in receiving-end systems. This paper mainly analyzes the role of ES in providing dynamic reactive power support. According to the different control modes of power conversion system (PCS), the ES is divided into grid-following (GFL) and grid-forming (GFM), and multi-infeed short circuit ratio (MISCR) considering both is constructed. The MISCR is taken as an objective function of the ES planning model. At the same time, the method of “accompanying network + model reconstruction” is proposed to realize the linearization calculation of MISCR. In order to compensate for the economic cost of ES investment, its energy storage function should also be used to participate in peak shaving during normal operation. Therefore, an ES planning model considering PCS selection is established, which including ES planning layer, system operation layer and accompanying network layer. Finally, the effectiveness of the proposed planning method is verified by a modified IEEE-39 system.